Dermatophyte infection: from fungal pathogenicity to host immune responses - Deng, Ruixin; Wang, Xiaowen; Li, Ruoyu (Frontiers in Immunology, 2023)
Dermatophytosis is a common superficial infection caused by dermatophytes, a group of pathogenic keratinophilic fungi. Apart from invasion against skin barrier, host immune responses to dermatophytes could also lead to pathologic inflammation and tissue damage to some extent. Therefore, it is of great help to understand the pathogenesis of dermatophytes, including fungal virulence factors and anti-pathogen immune responses. This review aims to summarize the recent advances in host-fungal interactions, focusing on the mechanisms of anti-fungal immunity and the relationship between immune deficiency and chronic dermatophytosis, in order to facilitate novel diagnostic and therapeutic approaches to improve the outcomes of these patients.